2020
DOI: 10.2147/ott.s249733
|View full text |Cite
|
Sign up to set email alerts
|

<p>Identification and Validation of Reference Genes Selection in Ovarian Cancer Exposed to Hypoxia</p>

Abstract: Introduction: Hypoxia-mediated tumor metastasis, progression and drug resistance are major clinical challenges in ovarian cancer. Meanwhile, the genetic basis of these traits is still not clear. RT-qPCR, as an efficient and sensitive gene expression technique, has been widely used for gene analyses, providing a basis for in-depth understanding of molecular changes in different microenvironments. However, there is currently a lack of suitable reference genes to normalize the data associated with hypoxia in ovar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 21 publications
0
5
0
Order By: Relevance
“…Loss of Rpl13a snoRNAs alters mitochondrial metabolism, reduces reactive oxygen species levels, increases glucose-stimulated insulin secretion from pancreatic islets, and enhances systemic glucose tolerance [ 72 ]. Previous studies have reported that under normoxic conditions, the most stably expressed genes in ovarian cancer cells are GAPDH/TBP, while under hypoxic conditions, the most stable candidate housekeeping genes are RPL13A/SDHA [ 73 ]. ITGAM encodes the α chain of integrin αMβ2 (CD11b).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of Rpl13a snoRNAs alters mitochondrial metabolism, reduces reactive oxygen species levels, increases glucose-stimulated insulin secretion from pancreatic islets, and enhances systemic glucose tolerance [ 72 ]. Previous studies have reported that under normoxic conditions, the most stably expressed genes in ovarian cancer cells are GAPDH/TBP, while under hypoxic conditions, the most stable candidate housekeeping genes are RPL13A/SDHA [ 73 ]. ITGAM encodes the α chain of integrin αMβ2 (CD11b).…”
Section: Discussionmentioning
confidence: 99%
“…Loss of Rpl13a snoRNAs alters mitochondrial metabolism, reduces reactive oxygen species levels, increases glucose-stimulated insulin secretion from pancreatic islets, and enhances systemic glucose tolerance [58]. Previous studies have reported that under normoxic conditions, the most stably expressed genes in ovarian cancer cells are GAPDH/TBP, while under hypoxic conditions, the most stable candidate housekeeping genes are RPL13A/SDHA [59]. With each new scienti c discovery, the structure of the GO resource continually evolves to incorporate biological knowledge of gene functions and to constantly improve its ability to re ect the latest state of biological understanding [70].…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this enzyme has been shown to be a key molecule in multiple biological functions, including molecular chaperoning,protein folding,protein tra cking,immune modulation,and cell signaling [6]. Studies have also reported that PPIA is involved in several diseases, including kawasaki disease [7],amyotrophic lateral sclerosis [8],atherosclerosis,myocardial infarction [9],severe sepsis [10],vascular smooth muscle cell disease [11],rheumatoid arthritis and HIV infection [12].Moreover,several studies have shown that PPIA is expressed in some cancers,including lung cancer,nasopharyngeal carcinoma [13],gastric adenocarcinoma [14],thyroid carcinoma [15],neuroblastoma [16],ovarian cancer [17],pancreatic cancer [18],breast cancer,colorectal cancer [19][20],melanoma [21],liver hepatocellular carcinoma [22].Many researchers have assessed PPIA function in cancer.It has been suggested that PPIA plays an important role in the whole pathological process of cancer development.High expression levels of PPIA were associated with decreased overall survival in liver hepatocellular carcinoma,colorectal cancer,low-grade glioma, acute myeloid leukemia.However,in gastric adenocarcinoma, high expression levels of CypA are positively correlated with invasiveness and distant metastasis.Therefore,both low and high expression of PPIA are associated with tumor prognosis.…”
Section: Introductionmentioning
confidence: 99%